2011
DOI: 10.1016/j.neuropharm.2010.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of α2-adrenergic receptors in the central nucleus of the amygdala attenuates stress-induced reinstatement of nicotine seeking in rats

Abstract: Tobacco addiction is a chronic disorder that is characterized by craving for tobacco products, withdrawal upon smoking cessation, and relapse after periods of abstinence. Previous studies demonstrated that systemic administration of α2-adrenergic receptor agonists attenuates stressinduced reinstatement of drug seeking in rats. The aim of the present experiments was to investigate the role of noradrenergic transmission in the central nucleus of amygdala (CeA) in stress-induced reinstatement of nicotine seeking.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 87 publications
4
69
1
Order By: Relevance
“…Individuals exposed to high levels of stress are more likely to relapse (Bruijnzeel and Gold, 2005). This is supported by the results of studies in laboratory animals showing that exposure to stress can reinstate nicotine seeking following extinction of operant responding (Buczek et al, 1999; Martin-García et al, 2009; Yamada and Bruijnzeel, 2011; Zislis et al, 2007). Animals trained to self-administer nicotine also display long-lasting increases in their responsivity to stress (Chen et al, 2008).…”
Section: Introductionmentioning
confidence: 68%
“…Individuals exposed to high levels of stress are more likely to relapse (Bruijnzeel and Gold, 2005). This is supported by the results of studies in laboratory animals showing that exposure to stress can reinstate nicotine seeking following extinction of operant responding (Buczek et al, 1999; Martin-García et al, 2009; Yamada and Bruijnzeel, 2011; Zislis et al, 2007). Animals trained to self-administer nicotine also display long-lasting increases in their responsivity to stress (Chen et al, 2008).…”
Section: Introductionmentioning
confidence: 68%
“…In a slightly later study, Glassman and colleagues also showed that clonidine was significantly efficacious in reducing nicotine withdrawal and promoting smoking cessation in women as compared to men (Covey & Glassman, 1991; Glassman et al, 1988), and particularly in vulnerable women (Glassman et al, 1993). Recent preclinical research holds support for these studies showing that intra central nucleus of the amygdala (CeA) infusion of clonidine and dexmedetomidine in rats, attenuates stress-induced reinstatement of nicotine seeking, possibly via synaptic connections between noradrenergic terminals and CRF neurons (Yamada & Bruijnzeel, 2011). …”
Section: The Role Of Guanfacine and Alpha-2 Receptor Agonists In Redumentioning
confidence: 99%
“…Neither bupropion nor varenicline, agents believed to modulate nicotine withdrawal symptoms and used to enhance the effectiveness of smoking cessation (125), have been studied in an ICU context. Others avenues are promising, such as the a^-adrenergic receptor agonists, dexmedetomidine and clonidine, have benefits in attenuating stress-induced nicotine craving in animal and human models (126)(127)(128) but clinical studies as to their effectiveness and safety are currently lacking.…”
Section: Nicotine Withdrawalmentioning
confidence: 99%